Análise arquitetural, ontológica e proposta de modelo de referência para a recomendação ITU-T G.805 - Barcelos, Pedro Paulo Favato (2011)
The ITU-T Recommendation G.805 (ITU-T, 2000) is an important recommendation for transport networks. It describes a generic functional architecture that is independent of technology for this domain and it is used as the basis for recommendations that describe the functional architecture of networks, management, performance analysis and functional specification of equipment. Despite providing a flexible tool for the architecture description, the recommendation presents its concepts textually, leading to confusion because of recursive definitions and unclear examples that are often contradictory. These aspects of the recommendation make it difficult to understand and may confuse the reader. It is important that, due to its fundamental importance, this recommendation is free from these problems. For this purpose, this work proposes the use of ontology-based conceptual modeling techniques for the generation of a reference model for the transport network domain, based on the ITU-T Recommendation G.805. In addition to the recommendation main concepts, the advantages of creating an ontology-based reference model and the main technologies used for this purpose are also presented. An architectural analysis and a restructuring of the components defined by the recommendation are performed together with an ontological evaluation of it. Cases of incompleteness, ambiguities and other deficiencies are checked and solutions are pointed. Finally, the ontology-based reference model developed for the ITU-T Recommendation G.805 is presented, including the conceptual model and its derivation and restrictions rules.